Influência dos amidos nativos e modificados nas propriedades físico-químicas e de textura da mortadela de frango - Scandolara, Christine (2017)
The manufacture of processed meat products represents an important part of the world meat industry. Within the range of emulsified meat products produced in the country are mortadella which are characterized by industrialized meat product, obtained from an emulsion of chicken, pork or beef, with or without added fat, added with ingredients, wrapped in wrapper Natural or artificial, and subjected to appropriate heat treatment, preserved or not at ambient temperature. The texture of this emulsion is the result of the interaction of animal fats with water, salt and meat proteins, in addition to starch, a polysaccharide used in large scale in emulsified meat products, for its geiliferative properties that aid in texture, water retention, consistency and stability of the products. The main starch available for this process is cassava, but its availability does not always meet the needs, thus, the industries need to look for alternatives to maintain the quality of the products, which can lead to difficulties in adapting other starches to the formulation. In this context, the objective of this work was to evaluate the use of four different types of starch in the chicken mortadella product and its behavior against texture, physico-chemical properties and shelf-life, in accordance with current legislation. For these evaluations four formulations with 5% starch were used. The starches were characterized by physical-chemical analysis, pulp properties by rapid viscosity analyzer (RVA-3D model, Newport Scientific, Australia), texture by texturometer equipment (model TA-XT plus, Stable Micro Systems, England). The physicochemical, pulp properties and texture properties of the gels of the studied starches show that starch A1 (cassava starch) presents more stability with less tendency to retrograde, more cohesiveness and gum. The embedded products were characterized by physical-chemical, microbiological, sensory and texture analysis in texturometer equipment (model TA-XT plus, Stable Micro Systems, England). The results showed that the use of the different types of starch did not affect the properties of mortadella when compared between them during the shef life, there was no alteration in the texture of the products and no influence of these on the analysis of water activity. Demonstrating a wider range of starches as an option for the food industry.